2022
DOI: 10.3390/pathogens11111242
|View full text |Cite
|
Sign up to set email alerts
|

Balantioides coli Fecal Excretion in Hunted Wild Cervids (Cervus elaphus and Dama dama) from Portugal

Abstract: Balantioides coli is a zoonotic enteric protozoan parasite of public veterinary health relevance and a concern in animal production and food safety. While wild cervids are recognized reservoirs for several zoonotic pathogens, little is known about the occurrence of B. coli in deer species, especially in Europe. To fill this gap, a total of 130 fecal samples from legally hunted red deer (Cervus elaphus, n = 95) and fallow deer (Dama dama, n = 35) were passively collected during two hunting seasons (October to F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…The B. coli prevalence of 14.6% found in the wild boar population studied was slightly higher than that from a study conducted in neighboring Spain, where an 11.7% prevalence rate was reported [1]. Interestingly, a recent study has identified B. coli in the wild cervids of Portugal [87], suggesting potentially different novel transmission routes. Nevertheless, the discrepancies observed in prevalence between the present study and the study mentioned before conducted in Spain may be explained, at least partially, by epidemiologic factors, as samples from the study were retrospectively studied up to 20 years ago.…”
Section: Discussioncontrasting
confidence: 69%
“…The B. coli prevalence of 14.6% found in the wild boar population studied was slightly higher than that from a study conducted in neighboring Spain, where an 11.7% prevalence rate was reported [1]. Interestingly, a recent study has identified B. coli in the wild cervids of Portugal [87], suggesting potentially different novel transmission routes. Nevertheless, the discrepancies observed in prevalence between the present study and the study mentioned before conducted in Spain may be explained, at least partially, by epidemiologic factors, as samples from the study were retrospectively studied up to 20 years ago.…”
Section: Discussioncontrasting
confidence: 69%
“…Even though none of our analyzed wild and domestic ungulate samples yielded positive results for B. coli, genotypes A and B were previously described in Portugal in red deer and wild boar [51,52], as well as in wild boar populations from Spain [41,44] and Poland [53] (Table 1). Contrary to the other free-ranging livestock species, pigs (B. coli primary host) are raised inside enclosures in the sampled areas, restricting their contact with wild boars, which can explain why we did not find this parasite in any of the analyzed samples.…”
Section: Prevalence Of Cryptosporidium Spp In Wild and Domesticmentioning
confidence: 70%
“…In Portugal, data on the occurrence and molecular diversity of these three enteric parasites in wild species are limited to the report of C. scrofarum in wild boar [51] and B. coli genotypes A and B in red deer and wild boar [51,52] (Table 1). Regarding domestic animals, G. duodenalis assemblages B, C, and D have been reported in dogs Canis lupus familiaris [86,87] and A, B, and E in cattle Bos taurus [101].…”
Section: Introductionmentioning
confidence: 99%
“…Data on the occurrence of G. duodenalis and B. coli in European hedgehogs are limited. While the presence of B. coli has not yet been confirmed in hedgehogs, its recent detection in wild animals from Portugal, including wild boars [40] and wild cervids [41], suggests the potential for this parasite to exist in the country's wildlife population. While G. duodenalis was not detected in the present study, its presence has been documented in other investigations.…”
Section: Discussionmentioning
confidence: 99%